Major Trends in Dalit Women’s Autobiographies in India (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
The hitherto marginalized peripheral Dalits in India have come up with their own voice to help them assume a central position in literature, and their voice is a voice of protest against their crass marginalization in a caste-ridden society. The most recent offshoot of Dalit literature is the autobiographies of Dalit women who have been subject to a double-edged oppression and exclusion by both the non-Dalit upper-caste people and the Dalit patriarchy. While these autobiographies are unique on more scores than one, they remain as a faithful antenna reflecting the dystopian asphyxiating suffering of Dalit women, and a historical document of it. This essay will try to situate these Dalit autobiographies in the socio-political context of the Indian Dalits, and attempt to identify some of the major trends in them. Finally, by drawing some seminal insights from subaltern studies, this essay will try to substantiate how the Dalit women’s individual voices articulated in these autobiographies repudiate Spivak’s controversial claim that the subalterns cannot speak.
Keywords: postcolonial; caste; Dalits; autobiographies; subaltern